Comparison of sexual functions in women with and without type 1 diabetes - DEMİRGÖZ BAL, MELTEM (My University, 2023)
OBJECTIVE: This study aimed to investigate female sexual function in patients with type 1 diabetes by comparing female sexual function index scores between women with and without type 1 diabetes. METHODS: A total of 62 women with type 1 diabetes and 69 age-matched women without diabetes but with similar backgrounds were enrolled in the patient and control groups, respectively. All participants were sexually active and had no systemic diseases other than diabetes in the patient group. RESULTS: The frequency of female sexual dysfunction was significantly higher, and the mean female sexual function index score was significantly lower in women with diabetes compared to the control group (p=0.01). There was a significant relationship between sexual dysfunction and duration of diabetes, glycosylated hemoglobin test, and body mass index (p<0.05). CONCLUSION: This study demonstrates that female sexual dysfunction is more common among women with type 1 diabetes than among women without type 1 diabetes. Patients with type 1 diabetes should be evaluated in terms of sexual health. Health professionals should give more attention to and provide guidance regarding sexual function in women with type 1 diabetes.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Diabetes mellitus; type 1. Sexuality. Sexual dysfunctions; psychological. Sexual dysfunction; physiological